Peningkatan Hasil Belajar Konfigurasi Elektron dengan Menggunakan KIT SELECTION (Smart Electron Configuration) - Anisa Fernanda; Eny Enawaty; Rahmad Rasmawan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This research was motivated by the low learning outcomes of students on the electron configuration subject matter at SMA negeri 2 Sungai Raya. This research aims to determine whether there was a difference in student learning outcomes between those who were given learning using KIT Selection media and those not on the electron configuration subject matter. Quasi experimental in the form of pretest-posttest control group design in the type of this study. The sample of this study were X IPA 2 as the control class and X IPA 3 as the experiment class. In experiment class, cooperative learning assisted by KIT Selection was given, whereas cooperative learning without KIT Selection was applied in control class. The result of U-Mann Whitney Test showed that the significant value of 0,004 < 0,05. Based on this result, it can be concluded that there was differences in learning outcomes between those who were given learning using KIT Selection media and those not on the electron configuration subject matter. The result of the Effect Size KIT Selection is 1,01 which is categorized as high and has an effect on learning outcomes by 34,38%.